Sport motivation and doping in adolescent athletes - Mudrak, Jiri (PLoS One, 2018)
BACKGROUND: Although performance-enhancing drugs appear to be prevalent in adolescent sports, relatively little attention has been paid to why adolescent athletes decide to use these drugs. In this study, we examine doping among adolescents from a motivational perspective and explore how motivational variables, such as achievement goal orientations and the perceived self-determination of sports activities, may be related to moral attitudes, doping intentions and doping behavior in adolescents who participate in competitive sports. METHODOLOGY: The study included 1035 adolescents participating in competitive sports from all regions of the Czech Republic (mean age = 16.3 years). The respondents completed a battery of questionnaires assessing their achievement goal orientations (task, ego), sports motivation at various levels of self-determination (intrinsic motivation, external regulation, amotivation), moral attitudes toward sport competition (acceptance of cheating, keeping winning in proportion, attitudes toward doping), doping intentions and doping behavior. A structural equation model was used to test the relations among motivational variables, attitudes, intentions and doping behavior. PRINCIPAL RESULTS: Our analyses indicated a good fit with the proposed model, which explained 59% of the variance in doping intentions and 17.6% of the variance in doping behavior. Within the model, task orientation was positively associated with intrinsic motivation and lower amotivation, whereas ego orientation was positively associated with extrinsic regulation and amotivation. Furthermore, intrinsic motivation was positively associated with keeping winning in proportion and negatively associated with acceptance of cheating and attitudes toward doping; the less self-determined forms of motivation showed opposite relationships. However, only the acceptance of cheating and attitudes toward doping were related to doping intention, which subsequently predicted doping behavior. CONCLUSIONS/SIGNIFICANCE: The results provide further evidence that sports motivation represents a psychological variable that should be considered in anti-doping policies, programs, and interventions aimed at the adolescent population because motivation was linked to the doping-related attitudinal variables and also partially mediated the effect of achievement goal orientations in this regard. On the basis of these results, we may argue that the focus on intrinsic enjoyment, self-referenced criteria of success and self-improvement may be related to more negative attitudes toward doping and cheating, lower doping intentions and less frequent doping behavior, whereas the emphasis on competition, comparison with others and external motivation appear to be related to the opposite outcomes.